2007
DOI: 10.1103/physrevlett.99.196601
|View full text |Cite|
|
Sign up to set email alerts
|

NaV2O4: A Quasi-1D Metallic Antiferromagnet with Half-Metallic Chains

Abstract: NaV 2 O 4 crystals were grown under high pressure using a NaCl flux, and the crystals were characterized with X-ray diffraction, electrical resistivity, heat capacity, and magnetization. The structure of NaV 2 O 4 consists of double chains of edge-sharing VO 6 octahedra. The resistivity is highly anisotropic, with the resistivity perpendicular to the chains more than 20 times greater than that parallel to the chains.Magnetically, the intrachain interactions are ferromagnetic and the interchain interactions are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…6) The X-ray diffraction measurement confirmed that NaV 2 O 4 is a mixed-valent V 3:5þ (3d 1:5 ) compound consisting of double chains of edgesharing VO 6 octahedra along the b axis. The intra-chain interaction is ferromagnetic while the inter-chain interaction is antiferromagnetic (AF), leading to the 3D AF order at around 140 K. NaV 2 O 4 exhibits a quasi-1D metallic nature below the AF transition temperature T N with the metallic conductivity parallel to the chains more than 20 times larger than that perpendicular to the chains.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…6) The X-ray diffraction measurement confirmed that NaV 2 O 4 is a mixed-valent V 3:5þ (3d 1:5 ) compound consisting of double chains of edgesharing VO 6 octahedra along the b axis. The intra-chain interaction is ferromagnetic while the inter-chain interaction is antiferromagnetic (AF), leading to the 3D AF order at around 140 K. NaV 2 O 4 exhibits a quasi-1D metallic nature below the AF transition temperature T N with the metallic conductivity parallel to the chains more than 20 times larger than that perpendicular to the chains.…”
Section: Introductionmentioning
confidence: 63%
“…6) The resistivity is highly anisotropic with the conductivity parallel to the chains more than 20 times larger than that perpendicular to the chains at very low temperatures. The anisotropy is gradually reduced in the AF state with increasing temperature while it becomes almost independent of temperature above T N .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a Heisenberg model of the zigzag ladder predicts degenerated ground states, including nematic, 3,4 topological, 5 chiral, 6 incommensurate magnetic orders, 7 the spin-Bose metal, 8 and the field-induced orbital current. 9 In the presence of the orbital degrees of freedom with the moderate electron correlation and the electron-phonon coupling, various phase transitions have been found, such as the valence bond 10,11 and ferromagnetic 12 orders in hollandites A 2 M 8 O 16 , and the antiferromagnetic metal 13 and insulator 14 in pyroferites AM 2 O 4 , where A are alkaline metals and M are transition metals. To understand these phase transitions, the electron correlation and the orbital occupancy would be the dominant parameters, which should be revealed experimentally.…”
Section: Introductionmentioning
confidence: 99%